2008
DOI: 10.1016/j.jacc.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

J-Point Elevation in Survivors of Primary Ventricular Fibrillation and Matched Control Subjects

Abstract: J-point elevation is found more frequently among patients with idiopathic VF than among healthy control subjects. The frequency of J-point elevation among young athletes is intermediate (higher than among healthy adults but lower than among patients with idiopathic VF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
379
8
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(432 citation statements)
references
References 32 publications
26
379
8
11
Order By: Relevance
“…Risk stratification ERP, known as notch or slur of the downsloping limb of the QRS complex, was considered long time a benign and innocent ECG phenomenon. The benign nature of ERP was challenged in 2000, based on experimental data showing that the presence of this ECG manifestation predisposes to the development of polymorphic ventricular tachycardia and ventricular fibrillation [11]. Validation of this hypothesis was provided 8 years later by Haissaguerre et al, Nam et al, and Rosso et al These studies, together with other case-control and population-based studies demonstrated the increased risk for development of malignant arrhythmias and sudden cardiac death in patients having ERP, especially localized in the inferior and infero-lateral leads.…”
Section: Molecular Basis Electrophysiological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk stratification ERP, known as notch or slur of the downsloping limb of the QRS complex, was considered long time a benign and innocent ECG phenomenon. The benign nature of ERP was challenged in 2000, based on experimental data showing that the presence of this ECG manifestation predisposes to the development of polymorphic ventricular tachycardia and ventricular fibrillation [11]. Validation of this hypothesis was provided 8 years later by Haissaguerre et al, Nam et al, and Rosso et al These studies, together with other case-control and population-based studies demonstrated the increased risk for development of malignant arrhythmias and sudden cardiac death in patients having ERP, especially localized in the inferior and infero-lateral leads.…”
Section: Molecular Basis Electrophysiological Backgroundmentioning
confidence: 99%
“…Rosso et al stated that the occurrence of a J wave on the surface ECG increases the probability of ventricular fibrillation from 3.4:100,000 to 11:100,000. [11][12][13][14][15] It is important to mention, that there are emerging data concerning the ventricular arrhythmia promoting effect of ERP in patients with chronic coronary heart disease and in the setting acute myocardial infarction [16,17].…”
Section: Molecular Basis Electrophysiological Backgroundmentioning
confidence: 99%
“…[2][3][4] From the second half of the 1990s, a growing number of case reports, case series, observational and prospective studies reported that the presence of various electrocardiographic patterns attributed to ER, but defined only by the presence of a J-point elevation with or without ST-segment displacement, may constitute a potential marker of increased risk of sudden death in otherwise normal subjects, casting a dark shadow on this ECG peculiarity. [5][6][7][8] Doubts about its real prognostic impact were emphasized even more during the preparticipation screening of competitive athletes, prompting the need for a broad cardiological evaluation, often including also an arrhythmological consultation with subsequent increase in costs.…”
Section: Clinical Perspective On P 1184mentioning
confidence: 99%
“…2,3,7,8 For this reason, the classical ER pattern found in athletes, by inference from the general population 2 and from short-term follow-up studies, 9 is considered benign. In contrast, evidence of an increased risk for sudden death exists for ER patterns characterized by J-point elevation associated with a horizontal/descending ST segment.…”
Section: Clinical Perspective On P 1184mentioning
confidence: 99%
“…Recently different studies have challenged this view and showed a significant association with life-threatening arrhythmias. [1][2][3][4][5] In 2008 Haïssaguerre et al first reported an increased prevalence of a particular pattern of ER on the resting 12-lead ECG of patients with history of idiopathic ventricular fibrillation (VF) (see Figure 1). 2 In these patients, ER was characterised by elevation of the QRS-ST segment junction of at least 0.1 mV above the baseline level, manifesting as QRS slurring (a smooth transition from the QRS complex to the ST segment) or notching (a positive J deflection of at least 1 mm inscribed on the S wave) in two adjacent inferior (II, III and aVF), lateral (I, aVL, and V4-V6), or infero-lateral leads.…”
mentioning
confidence: 99%